Cirrhosis etiology trends in developing countries: Transition from infectious to metabolic conditions. Report from a multicentric cohort in central Mexico - Alex Gonzalez-Chagolla; Antonio Olivas-Martinez; Jesus Ruiz-Manriquez; Maximiliano Servín-Rojas; Eric Kauffman-Ortega; Luis Carlos Chávez-García; Oscar Juárez-León; Jacqueline Cordova-Gallardo; Juan Daniel Díaz-García; Maria Sarai Gonzalez-Huezo; Guadalupe Milanés-Lizarraga; Victor M Paez-Zayas; et al. (Elsevier, 2022)
Summary: Background: Cirrhosis is a public health threat associated with high mortality. Alcoholic Liver Disease (ALD) is the leading cause in Latin America and Metabolic Associated Fatty Liver Disease (MAFLD) in western countries. In Mexico, ALD and chronic Hepatitis C Virus infection (HCV) were the most frequent aetiologies during the past decades. We aimed to describe the trends in the aetiologies of cirrhosis in a middle-income country. Methods: We performed a retrospective cohort study including patients diagnosed with cirrhosis between 2000 and 2019 from six different tertiary care hospitals in central Mexico. We collected information regarding cirrhosis etiology, year of diagnosis, hepatocellular carcinoma development, liver transplantation, and death. We illustrated the change in the tendencies of cirrhosis aetiologies by displaying the proportional incidence of each etiology over time stratified by age and gender, and we compared these proportions over time using chi square tests. Findings: Overall, 4,584 patients were included. In 2019, MAFLD was the most frequent cirrhosis etiology (30%), followed by ALD (24%) and HCV (23%). During the study period, MAFLD became the leading etiology, ALD remained second, and HCV passed from first to fourth. When analysed by gender, ALD was the leading etiology for men and MAFLD for women. The annual incidence of HCC was 3·84 cases/100 persons-year, the median survival after diagnosis was 12·1 years, and seven percent underwent LT. Interpretation: Increased alcohol consumption and the obesity epidemic have caused a transition in the aetiologies of cirrhosis in Mexico. Public health policies must be tailored accordingly to mitigate the burden of alcohol and metabolic conditions in developing countries. Funding: None.